Analisis Faktor Stres, Obesitas dan Kebiasaan Olah Raga Berhubungan dengan Kejadian Premenstrual Syndrome Pada Remaja Putri di SMP Negeri 1 Cijaku Kabupaten Lebak - Ramai Sri Litna; Novita Novita (Malahayati Nursing Journal, 2024)
ABSTRACT The incidence of premenstrual syndrome in Lebak Regency, one of which was carried out at SMAN 2 Cibeber, Lebak Regency, Banten was found to be around 54.8% women. Several factors associated with the occurrence of premenstrual syndrome include stress, obesity and exercise habits. Knowing the analysis of stress factors, obesity and exercise habits associated with the incidence of premenstrual syndrome in young women at SMP Negeri 1 Cijaku, Lebak Regency. Quantitative analysis with cross sectional design. The sample consisted of 63 young girls at SMP Negeri 1 Cijaku, Lebak Regency, using a purposive sampling technique. The instrument used is a questionnaire. Bivariate analysis using the chi square test. The results of the univariate study showed that most young women did not experience premenstrual syndrome 57.1%, did not experience stress 65.1%, were not obese 74.6%, and did not exercise routinely 54.0%. The results of the bivariate study found a significant relationship between stress (p value 0.000), obesity (p value 0.000) and exercise habits (p value 0.000) with the incidence of premenstrual syndrome in young women. There is a significant relationship between stress, obesity and exercise habits with the incidence of premenstrual syndrome in young women. Young women are expected to adopt a healthy lifestyle including exercising regularly, eating foods that are high in fiber, vitamins and protein, avoiding fast food, getting enough sleep and avoiding stress in order to avoid PMS incidents that can interfere with adolescent learning activities and activities. daughter. Keywords: Stress, Obesity, Exercise Habits, Premenstrual Syndrome, Young Women  ABSTRAK Kejadian premenstrual syndrome yang ada di Kabupaten Lebak salah satunya dilakukan di SMAN 2 Cibeber Kabupaten Lebak Banten ditemukan sekitar 54,8% perempuan. Beberapa faktor yang berhubungan dengan terjadinya premenstrual syndrome diantaranya stres, obesitas dan kebiasaan olah raga. Mengetahui analisis faktor stres, obesitas dan kebiasaan olah raga berhubungan dengan kejadian premenstrual syndrome pada remaja putri di SMP Negeri 1 Cijaku Kabupaten Lebak. Analitik kuantitatif dengan rancangan cross sectional. Sampel adalah remaja putri di di SMP Negeri 1 Cijaku Kabupaten Lebak sebanyak 63 sampel dengan teknik purposive sampling. Instrumen yang digunakan adalah kuesioner. Analisis bivariat menggunakan uji chi square. Hasil penelitian univariat sebagian besar remaja putri tidak mengalami kejadian premenstrual syndrome 57,1%, tidak stres 65,1%, tidak obesitas 74,6%, dan kebiasaan olah raga tidak rutin 54,0%. Hasil penelitian bivariat terdapat hubungan yang signifikan antara stres (p value 0,000), obesitas (p value 0,000) dan kebiasaan olah raga (p value 0,000) dengan kejadian premenstrual syndrome pada remaja putri. Terdapat hubungan yang signifikan antara stres, obesitas dan kebiasaan olah raga dengan kejadian premenstrual syndrome pada remaja putri. Remaja putri diharapkan dapat melakukan pola hidup sehat diantaranya dengan rutin melakukan olahraga, makan makanan yang mengandung tinggi serat vitamin dan protein, menghindari makanan cepat saji, istirahat tidur yang cukup dan menghindari stres agar dapat terhindar dari kejadian PMS yang dapat mengganggu aktivitas dan kegiatan belajar remaja putri. Kata Kunci: Stres, Obesitas, Kebiasaan Olah Raga, Kejadian Premenstrual Syndrome, Remaja Putri